Polyhydroxyurethane thermosets from novolac epoxide: Synthesis and its nanostructured blends with poly(trifluoroethylacrylate)-block-poly(N-vinylpyrrolidone) diblock copolymer. (20th January 2021) - Li, Lei; Ge, Wenming; Zhao, Bingjie; Adeel, Muhammad; Mei, Honggang; Zheng, Sixun
Abstract: A novel five-membered cyclic carbonate compound was synthesized via the reaction of novolac epoxide with carbon dioxide. The cyclic carbonate was then used as the precursor to prepare polyhydroxyurethane (PHU) thermosets with a trifunctional polyetheramine ( i.e., Jeffamine T 403) as the crosslinking agent. To improve the thermomechanical properties as well as hydrophobicity, the PHU thermosets were further nanostructured by the use of a poly(trifluoroethyl acrylate)- block -poly(N-vinylpyrrolidinone) (PTFEA- b -PVPy) diblock copolymer. Compared to plain PHU thermoset, the nanostructured thermosets displayed enhanced glass transition temperatures ( T g 's) and mechanical properties. Meanwhile, the surface hydrophobicity was significantly improved; the water surface contact angles of the thermosets have been increased up to 94.6°. With the introduction of PTFEA- b -PVPy, the nanostructured PHU thermosets still preserved the excellent shape memory and reprocessability at elevated temperature. Graphical abstract: Image 1 Highlights: Five-membered cyclic carbonate was synthesized from novolac epoxide and used as precursor of polyhydroxyurethane. Polyhydroxyurethane was modified by an amphiphilic block copolymer. The nanostructured polyhydroxyurethane thermosets displayed improved properties.